Shoot density, leaf removal and cluster thinning effects on microclimate, yield and fruit composition of the portuguese vine variety Touriga Nacional - Castro, Rogério (2013)
The evaluation of shoot density, basal leaf removal, and cluster thinning effects on canopy microclimate characteristics and their influence on yield and fruit composition, was carried out during 2 years (2005 to 2006) on one of the most important and noble Portuguese vine varieties – ‘Touriga Nacional’. The experimental field belongs to the private company Dão Sul, Soc. Vitivinícola, SA, located at Dão region, in centre of Portugal. The vineyard was grafted in 1991 onto 1103 P rootstock. The training system is bilateral Royat with vertical shoot positioning. Three different shoot densities were assayed (at G stage of Baggiolini scale): 23 shoots.m-1 row (D23), 17 shoots.m-1 row (D17) and 11 shoots.m-1 row (D11). At veraison, two other factors were introduced: leaf removal at fruit zone – LR1 (no leaf removal - LR0) and cluster thinning (30%) – CT1 (no cluster thinning – CT0). During the growing season several parameters were measured: leaf area, leaf water potential, leaf gas-exchanges, leaf layer number (LLN), canopy size, intercepted photosynthetically active radiation (PAR), fruit composition, yield and vigour. The reduction of shoot density and clusters thinning slightly improved the canopy microclimate, while basal leaf removal affected these parameters in a stronger way. Basal leaf removal didn’t affect any of the yield parameters. The yield was, however, significantly (p<0.05) reduced by cluster thinning and, in 2005, by the decreasing of shoot density. Concerning the grape composition, the studied factors didn’t significantly affect any of its parameters. These results may lead us to presume that no intervention on vineyard would be desirable. However, we verified that D23 treatment substantially increased pruning time (D23 – 88 hours/ha, D17 – 36 hours/ha, D11 – 29 hours/ha). This study indicates that the best option was the removal of water shoots on trunk and cordon - shoot density D17 without basal leaf removal or cluster thinning